Lithium ion battery pole piece and battery
By creating grooves on the active material layer of the lithium ion battery electrode sheet and increasing the diffusion channels and active sites of lithium ions, the problems of poor battery dynamics and cycling performance in the prior art are solved, and better electrolyte infiltration and energy density are achieved.
Patent Information
- Application Number
- CN202510194427.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-02-21
AI Technical Summary
The porosity of the active material layer of the existing lithium-ion battery electrode sheet is low, resulting in low in electrolyte infiltration and absorption efficiency, which in turn affects the lithium ion diffusion path and increases ion polarization, leading to poor battery dynamics, poor rate performance, poor cycle performance, easy lithium analysis and other problems, especially under low temperature and high current density conditions.
Multiple trenches are made on the active material layer of the electrode sheet, and a uniform trench structure is formed through laser processing technology, which increases the diffusion channel of lithium ions and the active sites of the graphite negative electrode with low specific surface area to form a denser SEI film and improves battery performance.
Through groove technology, the diffusion channels and active sites of lithium ions are improved, the infiltration effect of the electrolyte is improved, the circulating attenuation process is slowed, the energy density and circulating performance of the battery are improved, and the risk of lithium evolution is reduced.
Smart Images

Figure CN119812202A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of lithium-ion batteries, and specifically relates to a lithium-ion battery pole piece and a battery. Background Art
[0002] Lithium-ion batteries have high energy density and power density, making them the technology of choice for portable electronic devices, power tools, and hybrid / all-electric vehicles. Therefore, as consumers demand higher and higher product performance, the market demand for high-performance lithium-ion batteries is becoming more and more urgent.
[0003] The electrode plates of lithium-ion batteries are generally made by forming an active material layer on an electrode collector. Conventional electrode plates have low porosity in the active material layer, resulting in low electrolyte infiltration and absorption efficiency, increased ion diffusion paths in the electrode plates, increased ion polarization, and are prone to problems such as slow lithium ion migration and large battery internal resistance, that is, the kinetic performance of the electrochemical device is deteriorated, which further causes problems such as poor rate performance, poor cycle performance, and easy lithium precipitation of the electrochemical device. Especially under low-temperature charging and discharging and high current density conditions, lithium dendrites are more likely to form, which will also pose a greater hidden danger to the safety of the electrochemical device. In particular, as the thickness of the active material layer of the plate increases, such problems become more prominent.
[0004] Graphite is a common negative electrode material for lithium-ion batteries. The specific surface area of graphite material refers to the total area of graphite per unit mass. Graphite with a high specific surface area will lead to an increase in side reactions and a risk of reduced initial efficiency of electrochemical devices, while graphite with a low specific surface area has poor kinetic properties, which will cause lithium to precipitate on the negative electrode surface. In addition, its particle size is larger, the connection between particles is poor, and the SEI film formed is sparse and unstable, resulting in reduced cycle performance. Summary of the invention
[0005] In order to overcome the defects of the prior art, the present application provides a lithium-ion battery electrode and a battery.
[0006] The first aspect of the present application provides a lithium-ion battery pole piece, the pole piece includes a current collector, the current collector includes a first surface and a second surface opposite to each other along the thickness direction thereof, an active material layer is provided on the first surface, the surface of the active material layer has a plurality of grooves, the direction from the active material layer to the current collector along the thickness direction of the pole piece is a first direction, and when observed along the first direction, the total area of the plurality of grooves is 1%-10% of the surface area of the active material layer, and / or the total volume of the grooves in the active material layer is 0.05%-10% of the total volume of the negative electrode active material layer.
[0007] According to the pole piece of the first aspect, the active material layer has two or more grooves, and the plurality of grooves are arranged along the length direction of the pole piece.
[0008] According to the pole piece of the first aspect, the angle between the length direction of the groove and the length direction of the pole piece is 45° to 90°.
[0009] According to the pole piece of the first aspect, the cross-sectional shape of the groove perpendicular to its length direction is rectangular;
[0010] When viewed along the first direction, the groove shape is one of a rectangle, a parallelogram, and a trapezoid; and / or, the plurality of grooves are parallel to each other and are evenly distributed in the electrode active material layer along the length direction of the electrode.
[0011] According to the electrode sheet of the first aspect, the electrode sheet is a negative electrode sheet, and the active material layer is a negative electrode active material layer.
[0012] According to the pole piece of the first aspect, the groove satisfies the following formula:
[0013] 0.00001×V0≤V≤0.003×V0,
[0014] V=H×L×Y×L0 / (L+S),
[0015] V 0= B×m×H0,
[0016] Among them, the vertical distance between the deepest part of the groove and the surface of the electrode is H mm, the width of the groove on the surface of the electrode is L mm, the length of the groove on the surface of the electrode is Y mm, the length of the negative electrode active material layer is L0 mm, the spacing between two adjacent grooves is S mm, and the specific surface area of the negative electrode active material is B mm 2 / g, the coating mass of the negative electrode active material in the negative electrode active material layer is mg / mm 2 , the total volume of all the grooves is V mm 3 , the thickness of the negative electrode active material layer is H0, and 0<H <H0。
[0017] According to the pole piece of the first aspect, the groove width L on the pole piece surface also satisfies:
[0018] 0.1×Dv10≤L≤100×Dv90,
[0019] Wherein, Dv10 is the particle size corresponding to when the cumulative particle size distribution percentage of the negative electrode active material particles reaches 10%, and Dv90 is the particle size corresponding to when the cumulative particle size distribution percentage of the negative electrode active material particles reaches 90%.
[0020] According to the pole piece of the first aspect, the groove width L on the pole piece surface satisfies: 0.5×Dv10≤L≤50×Dv90.
[0021] According to the pole piece of the first aspect, the groove is perpendicular to the length direction of the pole piece.
[0022] According to the pole piece of the first aspect, the length of the groove on the pole piece surface is Y≤Y0, wherein Y0 is the width of the negative electrode active material layer.
[0023] According to the electrode sheet of the first aspect, the negative electrode active material is graphite.
[0024] According to the first aspect of the electrode sheet, the specific surface area B of the negative electrode active material is less than 3m 2 / g.
[0025] A second aspect of the present application provides a lithium-ion battery, which includes the pole piece of the first aspect.
[0026] The lithium-ion battery pole piece of the present application has but is not limited to the following beneficial effects:
[0027] The present application can increase the diffusion channels of lithium ions by making grooves on the pole pieces, especially the negative pole pieces, and making some channels, and can also increase the active sites of the low specific surface area graphite negative electrode, and avoid the problem of surface lithium sedimentation of low specific surface area graphite during the charging and discharging process. Grooving increases the reaction sites between graphite and electrolyte, and can form a denser SEI film, slow down the cycle attenuation process, and improve battery performance. By setting the relationship between the grooves and the active material layer, the electrolyte infiltration and energy density of the lithium-ion battery are further adjusted, so that the prepared pole piece has a good infiltration effect and a high energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 A schematic diagram of a lithium-ion battery electrode of the present application is shown, wherein: Figure 1 (a) shows a top view of the pole piece, Figure 1 (b) shows a cross-sectional view of a pole piece.
[0029] Figure 2 A schematic diagram of a lithium-ion battery electrode of the present application is shown, wherein: Figure 2 (a) shows a top view of the pole piece, Figure 2 (b) shows a cross-sectional view of a pole piece.
[0030] Description of reference numerals:
[0031] 1. Active material layer; 2. Current collector; 3. Groove; X-pole piece length direction; Y-pole piece width direction; Z-pole piece thickness direction (first direction). DETAILED DESCRIPTION
[0032] The present application is further described in detail below through the accompanying drawings and embodiments. Through these descriptions, the characteristics and advantages of the present application will become clearer and more specific.
[0033] The word "exemplary" is used exclusively herein to mean "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other embodiments. Although various aspects of the embodiments are shown in the drawings, the drawings are not necessarily drawn to scale unless otherwise noted.
[0034] In addition, the technical features involved in different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.
[0035] The present application provides a lithium-ion battery pole piece, which includes a current collector 2, at least one surface of the current collector 2 is provided with an active material layer 1, the surface of the active material layer 1 has a plurality of grooves 3, the direction from the active material layer 1 to the current collector 2 along the thickness direction of the pole piece is a first direction (Z-axis direction), and when observed along the first direction, the total area of the plurality of grooves 3 is 1%-10% of the surface area of the active material layer 1, and / or the total volume of the plurality of grooves 3 in the active material layer 1 is 0.05%-10% of the total volume of the active material layer 1.
[0036] The present application uses laser processing technology to manufacture a uniform groove structure in the active material layer of the pole piece, so that the lithium deposition and cycle attenuation of the battery are improved. The total area of the plurality of grooves 3 is 1%-10% of the surface area of the active material layer 1, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%. The larger the total area of the grooves accounts for the surface area of the active material layer 1, the better the diffusion effect of lithium ions. At the same time, when the total volume of the plurality of grooves 3 in the active material layer 1 accounts for the total volume of the active material layer 1, the ratio can be 0.05%-10%, for example, it can be 0.05%, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 2%, 5%, 8%, 10%, but when the total volume of the plurality of grooves 3 accounts for too large a proportion of the total volume of the active material layer 1, it will cause a large loss of battery volume energy density. The total volume of the plurality of grooves 3 in the active material layer 1 is preferably 0.05%-5% of the total volume of the negative electrode active material layer 1. In particular, the present application grooves the surface of the negative electrode sheet, which can increase the active sites of low specific surface area negative electrode active materials such as graphite negative electrodes and the diffusion channels of lithium ions, and overcome the problem of surface lithium precipitation of low specific surface area negative electrode active materials during charging and discharging. Grooving increases the reaction sites of low specific surface area graphite and electrolyte, and can form a denser SEI film to slow down the cycle attenuation process. When the number of grooves 3 in the negative electrode active material layer 1 is too large, the battery capacity will be reduced. If the number of grooves 3 in the negative electrode active material layer 1 is too small, it will not be able to provide active sites and diffusion channels, and the problem of lithium precipitation cannot be overcome.
[0037] In the present application, the total area of the grooves refers to the total area of the plurality of grooves 3 opened on the surface of the electrode piece measured along the first direction (Z-axis direction) on the surface of the active material layer, and the surface area of the active material layer 1 refers to the area of the surface of the active material layer 1 without grooves along the thickness direction of the electrode piece, that is, the projection area of the active material layer 1 on the current collector 2. The total volume of the grooves refers to the sum of the volumes of all grooves on the surface of the active material layer 1, for example, the volume of each groove 3 can be calculated by the length × width × height of the groove, and the total volume of the grooves is obtained by summing the volumes of all grooves; the total volume of the active material layer 1 refers to the volume of the active material layer 1 without grooves, for example, it can be calculated by the length × width × height of the active material layer 1 without grooves.
[0038] In one embodiment, the active material layer 1 has two or more grooves 3, and the plurality of grooves 3 are arranged along the length direction of the electrode piece;
[0039] Preferably, the angle between the length direction of the groove 3 and the length direction of the pole piece is 45° to 90°.
[0040] The present application does not particularly limit the shape of the groove 3, and the top view distribution shape of the groove 3 can be a straight line, a broken line, a curve, etc. Although the groove 3 on the surface of the active material layer 1 of the present application can be selected in any direction, considering the actual grooving process (such as laser grooving, mechanical grooving, etc.), multiple grooves 3 are arranged to be distributed in parallel for easy processing, reducing the difficulty of processing, and helping to improve the processing efficiency of the groove 3. The angle between the length direction of the groove 3 and the length direction of the pole piece is set to 45° to 90°. Compared with the case where the angle is less than 45°, the electrolyte can be infiltrated to the center of the pole piece through the groove 3 faster, thereby improving the infiltration effect.
[0041] In the embodiment of the present application, the parallel distribution of the grooves means that the axes of the length direction of any two grooves 3 (such as Figure 1 The left groove center is shown by the dotted line) and is parallel to each other, but due to process errors, measurement errors, etc., a certain angle is allowed between the axes of the two grooves, and the angle is ±5°. These embodiments are all included in the protection scope of the claims of this application.
[0042] In a preferred embodiment, the cross-sectional shape of the groove 3 perpendicular to its length direction is rectangular.
[0043] In a preferred embodiment, when viewed along the first direction, the shape of the groove 3 is a rectangle, a parallelogram, or a trapezoid.
[0044] In a preferred embodiment, the plurality of grooves 3 are parallel to each other and are evenly distributed in the active material coating area of the pole piece along the length direction of the pole piece.
[0045] In a specific embodiment, a plurality of grooves 3 are parallel to each other and evenly distributed on the surface of the active material layer 1 of the pole piece.
[0046] Through the above arrangement, multiple grooves 3 can be evenly distributed in the electrode active material layer 1, increasing the active sites and lithium ion diffusion channels on the electrode surface, so that the electrolyte can fully infiltrate the active material layer 1 and improve lithium precipitation.
[0047] Parallelism of the plurality of grooves 3 means that they are roughly parallel, and there are process tolerances within a range of ±10°. Uniform distribution means that the plurality of grooves 3 are distributed at roughly equal intervals, and there are process tolerances between the intervals within a range of ±0.3 mm.
[0048] Figure 1 A schematic diagram of a lithium-ion battery pole piece of the present application is shown, an active material layer 1 is formed on a current collector 2, and grooves are cut on the active material layer 1 to obtain grooves 3, wherein a plurality of grooves are distributed in parallel, an angle between the length direction of the groove 3 and the length direction of the pole piece (Y-axis direction) is 90°, and the length direction of the groove 3 is perpendicular to the length direction of the pole piece; the cross-sectional shape of the groove 3 in a direction perpendicular to its extension direction (X-axis direction, i.e., the width direction of the pole piece) is rectangular; when observed along a first direction (Z-axis direction), the shape of the groove 3 is rectangular; the grooves 3 are uniformly distributed in the active material coating area of the pole piece along the length direction (Y-axis direction) of the pole piece.
[0049] Figure 2 Another schematic diagram of the lithium-ion battery pole piece of the present application is shown, where the active material layer 1 is formed by coating the current collector 2, and grooves are formed on the active material layer 1 to obtain grooves 3, multiple grooves 3 are distributed in parallel, and the angle θ between the length direction of the groove 3 and the length direction of the pole piece (Y-axis direction) is 45°. The cross-sectional shape of the groove 3 perpendicular to its extension direction (X-axis direction, i.e., the width direction of the pole piece) is rectangular; when observed along the first direction (Z-axis direction), the shape of the groove 3 is a parallelogram and a trapezoid; the grooves 3 are evenly distributed in the pole piece active material layer along the length direction (Y-axis direction) of the pole piece.
[0050] In one embodiment, the electrode sheet is a negative electrode sheet, and the active material layer is a negative electrode active material layer.
[0051] In a specific embodiment, the groove 3 satisfies the following formula:
[0052] 0.00001×V0≤V≤0.003×V0,
[0053] V=H×L×Y×L0 / (L+S),
[0054] V 0= B×m×H0,
[0055] Among them, the vertical distance from the deepest part of the groove to the surface of the electrode tab is H mm, the width of the groove on the surface of the electrode tab is L mm, the length of the groove on the surface of the electrode tab is Y mm, the length of the negative active material layer is L0 mm, the spacing between two adjacent grooves is S mm, the specific surface area of the negative active material is B mm 2 / g, and the coating mass of the negative active material in the negative active material layer is m g / mm 2 , the total volume of all the grooves is V mm 3 , the thickness of the negative active material layer is H0, and 0 < H < H0. The preferred range of the depth is 0 < H ≤ 0.5H0.
[0056] Among them, V is the total volume of all the grooves (mm 3 ), H×L×Y is the volume of a single groove 3 (mm 3 ), L0 / (L + S) is the total number of grooves 3. The total volume V of all the grooves, the specific surface area B of the negative active material, the mass m of the negative active material in the negative active material layer 1, and the thickness H0 of the negative active material layer 1 satisfy the above relationship 0.00001×V0 ≤ V ≤ 0.003×V0. When V < 0.00001×V0, the total volume of multiple grooves 3 is too small to allow the electrolyte to fully infiltrate the electrode tab, resulting in lithium plating. When V > 0.003×V0, the total volume of the grooves 3 is too large, resulting in too little negative active material content, thus causing insufficient volumetric energy density. At the same time, as the depth of the groove 3 increases, the grooving process may cause a large thermal effect near the groove 3, causing the negative active material to fall off and form dust, resulting in an increase in the internal resistance of the battery, an imbalance in the electrochemical reaction, and even piercing of the separator, which has an adverse impact on the battery performance.
[0057] In this application, the vertical distance H from the deepest part of the groove 3 to the surface of the electrode tab can be measured by the following method: Cut the negative electrode tab and use a scanning electron microscope (SEM) to measure the vertical distance from the deepest part of the groove 3 to the surface of the electrode tab. Accumulate the numerical values of the vertical distances at 10 positions inside the groove 3 and take the average value to obtain the vertical distance H1 from the deepest part of the groove 3 to the surface of the electrode tab. In the case of having n grooves 3, use the same method to measure the vertical distances H2, H3,..., H n from the deepest parts of the other grooves 3 to the surface of the electrode tab n , and calculate the average value of the vertical distances H1~H
[0058] The width L of the groove on the pole piece surface can be obtained by the following test method: the pole piece is measured using a scanning electron microscope (SEM) to obtain the width of the groove on the pole piece surface, the values of 10 positions are measured cumulatively, and the average value is taken to obtain the groove width L1 of the pole piece surface of the groove 3. In the case of n grooves 3, the same method is used to measure the groove widths L2, L3, ..., L of other grooves 3. n , calculate the groove width L1~L of all grooves 3 on the pole piece surface n The average value of is L.
[0059] The length Y of the groove on the pole piece surface can be obtained by the following test method: the pole piece is measured using a scanning electron microscope (SEM) to obtain the length of the groove on the pole piece surface, and the values at 10 locations are measured cumulatively, and the average value is taken to obtain the length Y1 of the groove on the pole piece surface of the groove 3. When there are n grooves 3, the same method is used to measure the lengths Y2, Y3, ..., Y of the grooves on the pole piece surfaces of other grooves. n , calculate the length of the grooves Y1 to Y2 on the surface of all grooves 3 n The average value of is Y.
[0060] The spacing S between two adjacent grooves 3 can be obtained by the following test method: the pole piece is measured using a scanning electron microscope (SEM) to obtain the spacing between two adjacent grooves 3, and the values at 10 locations are measured cumulatively, and the average value is taken to obtain the spacing S1 of the two adjacent grooves. In the case of n grooves 3, the spacings S2, S3, ..., S1 of other two adjacent grooves 3 are measured by the same method. n-1 , calculate the lengths of the grooves S1 to S3 on the electrode surface of all grooves 3 n-1 The average value of is S.
[0061] In particular, if Figure 2 As shown, when observing along the first direction (Z-axis direction), that is, taking the thickness direction of the pole piece as the top-view perspective, when there is a certain angle between the length direction of the groove 3 and the length direction of the pole piece, the top-view shape of the groove 3 on the pole piece surface is a parallelogram or a trapezoid, the width L of the groove 3 on the pole piece surface is the distance between the two parallel walls formed by the groove and the active material layer 1, the spacing S between two adjacent grooves 3 is the vertical distance between the two adjacent walls of the two adjacent grooves 3, Y is the length of the center line of the two parallel walls formed by the groove 3 and the active material layer 1, and the straight line where the center line is located is the middle parallel line of the straight line where the two parallel walls are located. When the top-view shape of the groove 3 is a parallelogram, Y is the length of the above-mentioned two parallel walls, and when the top-view shape is a trapezoid, Y is the length of the median line of the trapezoid, as shown in FIG. Figure 2 Y' shown.
[0062] In the present application, when the grooves 3 are evenly distributed in parallel in the active material coating area, the parameters of the grooves 3 can be tested and obtained by the following method:
[0063] Random sampling is performed on the pole piece, the number of samples is 5, each sample has the same area, which can be adjusted according to the coverage of the active material layer 1, for example, 2cm×2cm, 3cm×3cm, 4cm×4cm, 5cm×5cm, 6cm×6cm, and cross-section and surface samples are prepared respectively, and the parameters of the groove 3 on the pole piece are detected by scanning electron microscopy (ZEISS Sigma / X-max). The depth H, width L, length Y, and spacing S of the groove 3 are respectively taken as the average value of 5 measurements.
[0064] In the present application, the length L0, width Y0 and thickness H0 of the active material layer 1 are all the thickness of a single layer of active material after cold pressing.
[0065] In the present application, the specific surface area (B) of graphite can be obtained by testing using the following method: using a specific surface area analyzer (TriStarⅡ3020X) to test, pre-treating the powder sample at 200°C / 2h before testing, and the testing environment is nitrogen.
[0066] In a specific embodiment, the groove width L on the surface of the negative electrode plate also satisfies:
[0067] 0.1×Dv10≤L≤100×Dv90, preferably, 0.5×Dv10≤L≤50×Dv90,
[0068] Wherein, Dv10 is the particle size corresponding to the cumulative particle size distribution percentage of the negative electrode active material particles reaching 10%, and Dv90 is the particle size corresponding to the cumulative particle size distribution percentage of the negative electrode active material particles reaching 90%. When the width L of the groove 3 is less than 0.1×Dv10, the width of the groove 3 is too small, which is not conducive to the infiltration of the electrolyte; when the width of the groove 3 is greater than 100×Dv90, the width of the groove 3 is too large, which will make the amount of the negative electrode active material too small, resulting in a decrease in the battery capacity.
[0069] In the present application, the particle size can be tested by the following method: Use a laser particle size tester (Malvern 2000) to test the particle size of graphite. Take about 5g of graphite powder sample in a 50ml clean beaker, add 1-2 drops of 1% surfactant P40, stir and soak the sample, then add about 20ml of water to make the powder completely dispersed in the water, and then put it into an ultrasonic cleaner with a power of 120W and a frequency of 53kHz for 5 minutes, stir evenly and then inject the sample for testing.
[0070] In the present application, the shape of the projection of the groove 3 along the first direction on the current collector can be regular or irregular, and both can achieve good results. The "width", "length" and "spacing" have conventional meanings in the art: the "width" can generally be understood as, when the shape of the projection of the groove 3 along the first direction on the current collector is a rectangle, the width is the width of the rectangle; when the shape of the projection of the groove 3 along the first direction on the current collector is non-rectangular, the width is the width equivalent to the width of a rectangle with the same area. The "length" can generally be understood as, when the shape of the projection of the groove 3 along the first direction on the current collector is a rectangle, the length is the length of the rectangle; when the shape of the projection of the groove 3 along the first direction on the current collector is non-rectangular, the length is the length equivalent to the length of a rectangle with the same area. The "spacing" refers to the shortest distance between the edges of two adjacent grooves 3.
[0071] In one embodiment, the groove 3 is perpendicular to the length direction of the pole piece;
[0072] Preferably, the length of the groove on the electrode surface is Y≤Y0, where Y0 is the width of the active material layer 1. The groove 3 of the present application is formed on the active material layer 1 and is restricted by the width of the active material layer 1, so the length of the groove 3 is Y≤Y0; at the same time, the change in the length of the groove 3 will also cause the total area and total volume of the groove 3 to change accordingly, thereby affecting the electrolyte infiltration effect and the volume energy density of the battery.
[0073] It should be noted that the perpendicularity between the groove 3 and the length direction of the pole piece means that the axis of the groove 3 in the length direction and the length direction of the pole piece (X-axis direction) are theoretically perpendicular to each other, that is, θ=90°. However, due to inevitable process errors, measurement errors, etc., there is a certain angle error between the groove 3 and the length direction of the pole piece (X-axis direction), and the error range is ±5°. Due to the expansion and contraction of the active material after cycling and the inevitable process errors, measurement errors, etc., the measurement error of the length, width, depth and spacing of the groove 3 after cycling is within ±5%. In one embodiment, the negative active material is graphite;
[0074] Preferably, the specific surface area B of the negative electrode active material is less than 3m 2 / g.
[0075] The present application also provides a method for preparing a lithium ion electrode, comprising:
[0076] (1) coating a negative electrode slurry containing an active material on one surface of a current collector 2 and cold pressing to form an active material layer 1;
[0077] (2) Grooving is performed on the surface of the active material layer 1 , preferably by using laser processing or mechanical processing.
[0078] The current collector 2 of the present application can be selected as a metal foil, such as copper foil, aluminum foil, etc.
[0079] In a specific embodiment, the electrode piece is a negative electrode piece.
[0080] In a specific embodiment, in step (1), the negative electrode slurry further includes a binder and / or a thickener;
[0081] Preferably, the binder is selected from one or more of the following: styrene-butadiene rubber latex SBR, styrene-propylene rubber, polyacrylic acid; and / or
[0082] Preferably, the thickener is selected from one or more of the following: sodium carboxymethyl cellulose, lithium carboxymethyl cellulose.
[0083] In one embodiment, in the negative electrode slurry, the mass percentage of the negative electrode active material is 94% to 98%.
[0084] The present application also provides a lithium-ion battery, which includes the aforementioned pole piece or a pole piece prepared according to the aforementioned method.
[0085] The present application has no special restrictions on the sources of all raw materials. Unless otherwise specified, they are all conventional products that can be obtained commercially.
[0086] Battery system
[0087] The battery system used in the comparative examples and embodiments uses lithium cobalt oxide as the positive electrode active material, graphite as the negative electrode active material, and a separator, electrolyte and packaging shell. It is manufactured through mixing, coating, assembly, injection and chemical formation processes. Among them:
[0088] (1) Positive electrode:
[0089] The positive electrode slurry of the battery is composed of 97.6% by mass of lithium cobalt oxide LiCoO2 as the positive electrode active material, 1.3% by mass of polyvinylidene fluoride (PVDF) as a binder, and 1.1% by mass of conductive carbon black SP as a conductive agent. The positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the coating weight is 235mg / 1540.25mm 2 , the thickness of the positive electrode active material layer after cold pressing is 36μm.
[0090] (2) Negative electrode:
[0091] The negative electrode slurry of the battery is mixed with 98% graphite as the negative electrode active material, 1.0% styrene butadiene rubber latex SBR as a binder, and 1.0% sodium carboxymethyl cellulose (CMC) as a thickener. The negative electrode slurry is coated on the negative electrode current collector 2 copper foil, and the coating weight is 130mg / 1540.25mm 2 The coating weight m of the negative electrode active material graphite is Y0×L0÷1540.25×130×98%=8.7061g / mm 2 The negative electrode sheet coating width Y0 is 71.7 mm, the length L0 is 1468 mm, and the thickness H0 of the negative electrode active material layer 1 after cold pressing is 44 μm. The surface area of the negative electrode active material layer 1 is Y0×L0=105255.6 mm 2 , the total volume of the negative electrode active material layer 1 is Y0×L0×H0=4631.25mm 3 .
[0092] (3) Electrolyte:
[0093] The electrolyte is a solution prepared by mixing LiPF6 and a solvent (the mass ratio of ethylene carbonate: diethyl carbonate: methyl ethyl carbonate: vinylene carbonate is 8:85:5:2) in a mass ratio of 8:92.
[0094] (4) Diaphragm:
[0095] The base material of the isolation film is a 9μm thick polypropylene diaphragm, and the thickness of the adhesive layer is 15μm.
[0096] The negative electrode sheet, separator and positive electrode sheet are stacked in order, and then wound to form a bare cell, which is then packaged, injected (i.e., injected with electrolyte) and left to stand to obtain a cell that is fully soaked, and then subjected to steps such as formation to obtain a lithium-ion battery.
[0097] The charging limit voltage U of the batteries in the comparative examples and embodiments of the present application is 4.5V, which illustrates that the electrode processing method of the present application can be applied to batteries of various voltage systems, and is not limited to the 4.5V system. By comparing the negative electrode processing method in the prior art (without laser processing) used in the comparative example with the laser processing method for the electrode used in the embodiment provided by the present application, the lithium deposition interface after 10 cycles and the capacity retention rate after 500 cycles are compared.
[0098] Examples and Comparative Examples
[0099] According to the parameters in Table 1, grooves are cut on the active material layer of the electrode using laser processing.
[0100] Laser processing method: fiber laser processing is adopted, laser process parameters: power: 10%~90%, laser speed: 1000~70000mm / s.
[0101] Groove parameters obtained in various embodiments and comparative examples and performance tests of lithium-ion batteries
[0102] The performance of the lithium-ion batteries and the positive / negative electrode plate groove parameters prepared in each embodiment and comparative example was tested by the following method, and the test results are listed in Table 2.
[0103] 1. Comparison method of lithium deposition interface:
[0104] When the test environment temperature is 25°C, the batteries of the comparative example and the embodiment are charged and discharged 10 times using the same charging process, and then the batteries are disassembled to compare and observe the negative electrode plates to obtain the lithium deposition interface. Charging process:
[0105] Step 1: Charge the battery to 4.5V at 2C constant current;
[0106] Step 2: Charge the battery to 0.05C at a constant voltage of 4.5V;
[0107] Step 3: Let the battery sit for 5 minutes;
[0108] Step 4: Discharge the battery to 3.0V at 0.5C constant current;
[0109] Step 5: Let the battery sit for 5 minutes;
[0110] Step 6: Repeat steps 1 to 5 10 times.
[0111] The battery cells that have been cycled 10 times are disassembled and the interface of the negative electrode plate is compared and observed. In order to describe the lithium deposition at the cycle interface, the interface conditions are now graded. Through naked eye observation by operators, if the surface of the negative electrode plate is golden and there is no abnormality, it is judged as no lithium deposition; if the negative electrode plate has intermittent purple spots, lithium deposition, or lithium deposition on purple spots, it is judged as slight lithium deposition; if the main body of the negative electrode plate has large-area continuous purple spots, lithium deposition, or lithium deposition on purple spots, and the abnormal area accounts for <50%, it is judged as lithium deposition; if the main body of the negative electrode plate has large-area continuous purple spots, lithium deposition, or lithium deposition on purple spots, and the abnormal area accounts for ≥50%, it is judged as severe lithium deposition.
[0112] 2. Cycle performance test of lithium-ion batteries:
[0113] The calculation method of the capacity retention rate includes: when the test environment temperature is 25°C, the batteries of the comparative example and the embodiment are charged and discharged 500 times using the same charging process, and then the discharge capacity of the battery after 500 cycles of charge and discharge is divided by the discharge capacity of the battery at the first cycle to obtain the capacity retention rate. Charging process:
[0114] Step 1: Charge the battery to 4.5V at 2C constant current;
[0115] Step 2: Charge the battery to 0.05C at a constant voltage of 4.5V;
[0116] Step 3: Let the battery sit for 5 minutes;
[0117] Step 4: Discharge the battery to 3.0V at 0.5C constant current;
[0118] Step 5: Let the battery sit for 5 minutes;
[0119] Step 6: Repeat steps 1 to 5 above 500 times.
[0120] 3. Battery volume energy density test:
[0121] The test methods for volume energy density include:
[0122] Capacity test of battery cells: let the battery cells stand at 25℃ for 30min, ensure that the temperature of the battery cells is 25℃, and then discharge the battery at a constant current of 0.2C to 3.0V; after standing for 10min, charge the battery cells at a constant current of 0.5C to 4.53V, continue to charge at a constant voltage of 4.53V until the current is 0.02C, let stand for 10min, discharge the battery cells at a constant current of 0.2 to 3.0V, and record the discharge capacity C and discharge platform voltage U of the battery cells in this discharge step.
[0123] Battery cell volume measurement:
[0124] Use a caliper to measure the length, width, and height of the battery's outer surface and calculate the volume V of the single battery d .
[0125] Volume energy density calculation: E = C × U / V d , unit is Wh / L.
[0126] Table 1
[0127]
[0128]
[0129] Table 2
[0130]
[0131]
[0132] From the above test results we can see that:
[0133] (1) By comparing the ungrooved comparative examples 1 and 2 with examples 1-17, the electrode groove treatment can improve the lithium deposition interface and cycle retention rate; by comparing comparative examples 1 and 2, it can be seen that the specific surface area B of the negative electrode active material is less than 3m 2 / g, the lithium deposition interface can be improved.
[0134] (2) By comparison of Examples 1-17, when the groove parameters of the electrode plate treated by laser satisfy the corresponding relationship, the active sites of the low specific surface area graphite negative electrode and the diffusion channels of lithium ions are increased, thereby improving the surface lithium plating problem of the low specific surface area graphite during the charge and discharge process, and significantly improving the lithium plating interface and cycle capacity retention rate of the battery.
[0135] When the groove area on the electrode surface is larger, the electrolyte transmission paths in all directions become more numerous, and the improvement is more significant. When the total volume of the groove 3 is larger, the battery volume energy density loss is larger, so there is an optimal range for each parameter.
[0136] In Comparative Examples 1 and 2, the surface wetting effect of the ungrooved pole piece is poor, resulting in the occurrence of lithium deposition, and the capacity retention rate is also significantly reduced compared with the embodiment using graphite, a negative electrode material with a similar surface area; in Comparative Example 3, the groove width is too narrow, resulting in a small ratio of the total volume of the groove 3 to the total volume of the negative electrode active material layer 1, resulting in serious lithium deposition on the pole piece; in Comparative Examples 3 and 4, the groove width is too narrow, not only resulting in a small ratio of the total volume of the groove 3 to the total volume of the negative electrode active material layer 1, but also resulting in V < 0.00001 × V0, In Ratio 3, 0.00001×V0=3.064547, V=0.3154513; in Comparative Example 4, 0.00001×V0=3.064547, V=1.31241397, resulting in severe lithium deposition on the electrode and low capacity retention rate; in Comparative Example 5, 0.3×V0=919.36416, V=935.6053, V>0.003×V0, the excessive groove volume leads to excessive loss of active substances on the electrode surface, which significantly reduces the energy density of the battery.
[0137] Similarly, in the embodiment, when the ratio of the total volume of the grooves 3 to the total volume of the negative electrode active material layer 1 is too small, the reaction sites of the graphite and the electrolyte on the surface of the electrode are less increased, and lithium deposition still occurs; and when the ratio of the total volume of the grooves 3 to the total volume of the active material is too large, it will lead to a decrease in the volume energy density of the battery. The embodiments within the above preferred range have better wetting effect, capacity retention rate and energy density.
[0138] In summary, the processing method of the electrode of the present application increases the reaction sites between graphite and electrolyte, and within the preferred parameter range, can improve the lithium deposition interface and slow down the cycle attenuation process.
[0139] The present application has been described above in conjunction with preferred embodiments, but these embodiments are only exemplary and serve only as an illustration. On this basis, various replacements and improvements may be made to the present application, all of which fall within the scope of protection of the present application.
Claims
1. A lithium-ion battery pole piece, characterized in that: The pole piece includes a current collector, and the current collector includes a first surface and a second surface opposite to each other along the thickness direction thereof, the first surface is provided with an active material layer, the surface of the active material layer has a plurality of grooves, and the direction from the active material layer to the current collector along the thickness direction of the pole piece is a first direction, and when observed along the first direction, the total area of the plurality of grooves is 1%-10% of the surface area of the active material layer, and / or the total volume of the grooves in the active material layer is 0.05%-10% of the total volume of the active material layer.
2. The pole piece according to claim 1, characterized in that: The plurality of grooves are arranged along the length direction of the pole piece.
3. The pole piece according to claim 1, characterized in that: The angle between the length direction of the groove and the length direction of the pole piece is 45° to 90°.
4. The pole piece according to claim 3, characterized in that: The cross-sectional shape of the groove perpendicular to its length direction is rectangular; When viewed along the first direction, the groove has a shape of a rectangle, a parallelogram, or a trapezoid; and / or, a plurality of the grooves are parallel to each other and are evenly distributed in the active material layer along the length direction of the pole piece.
5. The pole piece according to any one of claims 1 to 4, characterized in that: The pole piece is a negative pole piece, and the active material layer is a negative active material layer.
6. The pole piece according to claim 4, characterized in that: The groove satisfies the following formula: 0.00001×V0≤V≤0.003×V0, V=H×L×Y×L0 / (L+S), In 0= B×m×H0, Among them, the vertical distance between the deepest part of the groove and the surface of the electrode is H mm, the width of the groove on the surface of the electrode is L mm, the length of the groove on the surface of the electrode is Y mm, the length of the negative electrode active material layer is L0 mm, the spacing between two adjacent grooves is S mm, and the specific surface area of the negative electrode active material is B mm 2 / g, the coating mass of the negative electrode active material in the negative electrode active material layer is mg / mm 2 , the total volume of all the grooves is V mm 3 , the thickness of the negative electrode active material layer is H0, and 0<H <H0。 7. The pole piece according to claim 6, characterized in that: The groove width L on the pole piece surface also satisfies: 0.1×Dv10≤L≤100×Dv90, Wherein, Dv10 is the particle size corresponding to when the cumulative particle size distribution percentage of the negative electrode active material particles reaches 10%, and Dv90 is the particle size corresponding to when the cumulative particle size distribution percentage of the negative electrode active material particles reaches 90%.
8. The pole piece according to claim 7, characterized in that: The groove width L on the pole piece surface satisfies: 0.5×Dv10≤L≤50×Dv90.
9. The pole piece according to any one of claims 6 to 8, characterized in that: The groove is perpendicular to the length direction of the pole piece.
10. The pole piece according to claim 9, characterized in that: The length of the groove on the surface of the pole piece is Y≤Y0, wherein Y0 is the width of the negative electrode active material layer.
11. The pole piece according to claim 6, characterized in that: The negative electrode active material is graphite.
12. The pole piece according to claim 11, characterized in that: The specific surface area B of the negative electrode active material is less than 3m 2 / g.
13. A lithium ion battery comprising the pole piece according to any one of claims 1 to 12.
Citation Information
Patent Citations
Electrode pole plate of lithium ion battery, pole plate rolling device and lithium ion battery
CN106531961A
Electrode for lithium secondary battery and lithium secondary battery
JP2008277242A
Secondary cell and its manufacturing method
US20100279158A1
Electrode for secondary battery and secondary battery including same
US20220293918A1
Cited By
Lithium-ion battery electrode sheet and lithium-ion battery
WO2026174902A1